Evaluation of tear production using ocular surface imaging - Ithnin, Mohd. Hafidz; Mohd Kamal, Khairidzan; Ariffin, Azrin Esmady (Faculty of Medicine, University of Malaya, 2017)
Introduction: Schirmer test is mainly used for measuring tear production. The purpose of this study is to assess the production of tears using ocular surface imaging.